Oxidation and degradation of polypropylene transvaginal mesh. Issue 5 (24th March 2017) - Talley, Anne D.; Rogers, Bridget R.; Iakovlev, Vladimir; Dunn, Russell F.; Guelcher, Scott A.
Abstract: Polypropylene (PP) transvaginal mesh (TVM) repair for stress urinary incontinence (SUI) has shown promising short-term objective cure rates. However, life-altering complications have been associated with the placement of PP mesh for SUI repair. PP degradation as a result of the foreign body reaction (FBR) has been proposed as a contributing factor to mesh complications. We hypothesized that PP oxidizes under in vitro conditions simulating the FBR, resulting in degradation of the PP. Three PP mid-urethral slings from two commercial manufacturers were evaluated. Test specimens ( n = 6) were incubated in oxidative medium for up to 5 weeks. Oxidation was assessed by Fourier Transform Infrared Spectroscopy (FTIR), and degradation was evaluated by scanning electron microscopy (SEM). FTIR spectra of the slings revealed evidence of carbonyl and hydroxyl peaks after 5 weeks of incubation time, providing evidence of oxidation of PP. SEM images at 5 weeks showed evidence of surface degradation, including pitting and flaking. Thus, oxidation and degradation of PP pelvic mesh were evidenced by chemical and physical changes under simulated in vivo conditions. To assess changes in PP surface chemistry in vivo, fibers were recovered from PP mesh explanted from a single patient without formalin fixation, untreated ( n = 5) or scraped ( n = 5) to remove tissue, and analyzed by X-ray photoelectron spectroscopy. Mechanical scraping removed adherent tissue, revealing an underlying layer of oxidized PP. These findings underscore the need for further research into the relative contribution of oxidative degradation to complications associated with PP-based TVM devices in larger cohorts of patients.